Polymineralic inclusions in oxide minerals of the Afrikanda alkaline-ultramafic complex: Implications for the evolution of perovskite mineralisation - Potter, NJ; Vadim Kamenetsky; Chakhmouradian, AR; Maya Kamenetsky; Karsten Goemann; Thomas Rodemann (2020)
The exceptional accumulation of perovskite in the alkaline-ultramafic Afrikanda complex (Kola Peninsula, Russia) led to the study of polymineralic inclusions hosted in perovskite and magnetite to understand the development of the perovskite-rich zones in the olivinites, clinopyroxenites and silicocarbonatites. The abundance of inclusions varies across the three perovskite textures, with numerous inclusions hosted in the fine-grained equigranular perovskite, fewer inclusions in the coarse-grained interlocked perovskite and rare inclusions in the massive perovskite. A variety of silicate, carbonate, sulphide, phosphate and oxide phases are assembled randomly and in variable proportions in the inclusions. Our observations reveal that the inclusions are not bona fide melt inclusions. We propose that the inclusions represent material trapped during subsolidus sintering of magmatic perovskite. The continuation of the sintering process resulted in the coarsening of inclusion-rich subhedral perovskite into inclusion-poor anhedral and massive perovskite. These findings advocate the importance of inclusion studies for interpreting the origin of oxide minerals and their associated economic deposits and suggest that the formation of large scale accumulations of minerals in other oxide deposits may be a result of annealing of individual disseminated grains.